Bioabsorbable particles and methods of use

Biological absorption particles with a polymer matrix and cationic lipids efficiently deliver anti-sense oligonucleotides to the colon, addressing delivery challenges and treating inflammatory diseases by targeted release.

JP2025502716AInactive Publication Date: 2025-01-28WL GORE & ASSOC INC +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024537961
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-02
Filing Date
2022-12-20
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Delivering active agents, such as nucleic acids, to the colon for treating inflammatory diseases like IBD is challenging due to environmental and physiological barriers, including mucus and epithelial layers.

Method used

Biological absorption particles comprising a polymer matrix encapsulating anti-sense oligonucleotides (ASO) and cationic lipids, with a size less than 300 nm, are designed to overcome these barriers by being absorbed in the colon, where the polymer matrix decomposes, releasing the nucleic acids for treatment.

Benefits of technology

The particles effectively deliver nucleic acids to the colon, treating inflammatory diseases by ensuring targeted and efficient release of therapeutic agents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502716000001_ABST
    Figure 2025502716000001_ABST
Patent Text Reader

Abstract

The present disclosure provides bioabsorbable particles that include nucleic acids. The bioabsorbable particles also include a bioabsorbable polymer matrix and a lipid salt, both of which can be modified to affect the properties of the particle. The bioabsorbable particles can be administered to a patient for the treatment of a disease. Methods of making and using the bioabsorbable particles are also provided.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Field The present disclosure relates generally to bioabsorbable particles. More specifically, the present disclosure relates to particles comprising a polymer, a lipid salt and a nucleic acid agent for therapeutic use. [Background technology]

[0002] background Numerous developments in the medical field have led to new techniques to combat diseases. One such development is the use of active agents containing nucleic acids to treat inflammatory diseases such as inflammatory bowel disease (IBD). However, delivering active agents to the colon for the treatment of IBD can be difficult due to physiological challenges, biochemical barriers, and environmental barriers, including those associated with mucus and epithelium. Summary of the Invention

[0003] Abstract In one embodiment ("Embodiment 1"), the formulation comprises a plurality of bioabsorbable particles, each bioabsorbable particle comprising a polymer matrix, an antisense oligonucleotide (ASO) encapsulated within the polymer matrix, and a cationic lipid encapsulated within the polymer matrix, wherein the plurality of bioabsorbable particles comprises at least about 1 weight percent of the antisense oligonucleotide (ASO).

[0004] In another embodiment ("embodiment 2"), further to embodiment 1, the plurality of bioabsorbable particles have an average particle size of less than 300 nm.

[0005] In another embodiment (“Embodiment 3”), further to any one of embodiments 1 or 2, the plurality of bioabsorbable particles comprises at least about 5 weight percent ASO.

[0006] In another embodiment ("Embodiment 4"), further to any one of embodiments 1-3, the plurality of bioabsorbable particles comprises at least about 10 weight percent ASO.

[0007] In another embodiment (“Embodiment 5”), further to any one of embodiments 1-4, the plurality of bioabsorbable particles comprises at least about 15 weight percent ASO.

[0008] In another embodiment ("Embodiment 6"), in addition to any one of embodiments 1-5, the polymer matrix includes trimethylene carbonate (TMC).

[0009] In another embodiment ("Embodiment 7"), in addition to any one of embodiments 1-6, the polymer matrix comprises a copolymer of TMC and polylactic acid (PLA).

[0010] In another embodiment ("Embodiment 8"), further to embodiment 7, the ratio of TMC / PLA is about 25 / 75.

[0011] In another embodiment ("Embodiment 9"), in addition to any one of embodiments 1-8, the polymer matrix comprises a poly(lactic-co-glycolic acid) (PLGA) copolymer.

[0012] In another embodiment ("embodiment 10"), any one of embodiments 1-9 further comprises a surface polymer attached to a surface of each of said bioabsorbable particles.

[0013] In another embodiment ("embodiment 11"), in addition to embodiment 10, the surface polymer comprises polyethylene glycol (PEG).

[0014] In another embodiment ("Embodiment 12"), in addition to embodiment 11, the bioabsorbable particles comprise at least 5 weight percent PEG.

[0015] In another embodiment ("Embodiment 13"), in addition to any one of embodiments 1-12, the plurality of bioabsorbable particles comprises between about 10 weight percent and about 40 weight percent cationic lipid.

[0016] In another embodiment ("Embodiment 14"), in addition to any one of embodiments 1-13, the plurality of bioabsorbable particles comprises about 20 percent to about 30 percent by weight of cationic lipid.

[0017] In another embodiment ("Embodiment 15"), in addition to any one of embodiments 1-14, the plurality of bioabsorbable particles comprises nanoparticles.

[0018] In another embodiment ("Embodiment 16"), in addition to any one of embodiments 1-14, the plurality of bioabsorbable particles comprises microparticles.

[0019] In one embodiment ("Embodiment 17"), a method of treating a patient in need thereof comprises delivering to the patient a formulation of any of embodiments 1-16 and allowing sufficient time for the polymer matrix to degrade in the patient and release the nucleic acid in the patient.

[0020] In one embodiment ("Embodiment 18"), a method of making a bioabsorbable particle formulation includes dissolving a structural polymer and a cationic lipid in a solvent, adding a nucleic acid of 2-75 nucleotides in length to the dissolved structural polymer and cationic lipid, sonicating the mixture of structural polymer, cationic lipid, and nucleic acid in a first sonication to create a water-in-oil emulsion, adding an aqueous solution to the water-in-oil emulsion, sonicating the water-in-oil emulsion in a second sonication to produce a water-in-oil-in-water emulsion, adding water to the water-in-oil-in-water emulsion, collecting a plurality of particles from the water-in-oil-in-water emulsion, and washing the plurality of particles.

[0021] In another embodiment ("embodiment 19"), in addition to embodiment 18, the cationic lipid and the structural polymer are dissolved in a mass ratio of about 1:4 to about 1:1.

[0022] In another embodiment ("embodiment 20"), further to embodiment 18 or 19, the nucleic acid is an antisense oligonucleotide (ASO) and is supported on the plurality of particles at about 5 weight percent to about 20 weight percent.

[0023] In another embodiment ("Embodiment 21"), in addition to any one of embodiments 18-20, the first sonication and the second sonication are completed in an ice bath.

[0024] In another embodiment ("embodiment 22"), in addition to any one of embodiments 18-21, the aqueous solution is a polyvinyl alcohol solution.

[0025] In another embodiment ("Embodiment 23"), in addition to any one of embodiments 18-22, the step of collecting the plurality of particles from the emulsion is completed by centrifugation.

[0026] In another embodiment ("embodiment 24"), the method comprises any one of embodiments 18-23, plus lyophilizing the oil solution in the presence of a sugar and a buffer.

[0027] In another embodiment ("embodiment 25"), in addition to embodiment 24, the sugar is trehalose.

[0028] In another embodiment ("embodiment 26"), in addition to embodiment 24 or 25, the buffer is histidine.

[0029] In one embodiment ("Embodiment 27"), a method of treating a patient in need of treatment includes (1) delivering to the patient a plurality of particles, each particle comprising a polymer matrix, a nucleic acid encapsulated within the polymer matrix, the nucleic acid being 2 to 75 nucleotides in length, and a cationic lipid encapsulated within the polymer matrix, wherein the ratio of the cationic lipid to the polymer matrix in each particle is about 1:4 to about 1:1 by mass, and (2) allowing a sufficient time for the polymer matrix to biodegrade within the patient and release the nucleic acid.

[0030] In another embodiment ("Embodiment 28"), further to embodiment 27, the nucleic acid is an antisense oligonucleotide (ASO) loaded into the plurality of particles at about 5 weight percent to about 20 weight percent, and the cationic lipid is either 1,2-di-O-octadecenyl-3-trimethylammonium propane chloride salt (DOTMA) or 1,2-dioleoyl-3-trimethylammonium propane chloride salt (DOTAP).

[0031] In another embodiment ("embodiment 29"), further to embodiment 27 or 28, the polymer matrix biodegrades in the colon of the patient.

[0032] In another embodiment ("embodiment 30"), in addition to any one of embodiments 27-29, each particle further comprises a surface polymer on a surface of each particle, said surface polymer comprising polyethylene glycol (PEG).

[0033] In another embodiment ("Embodiment 31"), further to embodiment 30, each particle comprises at least 5 wt% PEG.

[0034] In another embodiment ("embodiment 32"), in addition to any one of embodiments 27-31, the plurality of particles comprises nanoparticles.

[0035] In another embodiment ("Embodiment 33"), in addition to any one of embodiments 27-32, the patient has at least one of inflammatory bowel disease, cardiovascular disease, hypertension, chronic heart failure, diabetes, Parkinson's disease, prostate cancer, and chronic kidney disease.

[0036] In one embodiment ("Embodiment 34"), the formulation comprises a plurality of bioabsorbable particles, each bioabsorbable particle comprising a polymer matrix, a nucleic acid encapsulated within the polymer matrix, a cationic lipid encapsulated within the polymer matrix, and a surface polymer attached to a surface of each bioabsorbable particle, the surface polymer comprising polyethylene glycol (PEG), and each bioabsorbable particle comprising at least 5 percent by weight PEG. [Brief description of the drawings]

[0037] BRIEF DESCRIPTION OF THE DRAWINGS The accompanying drawings are included to provide a further understanding of the disclosure, and are incorporated in and constitute a part of this specification, illustrating embodiments and, together with the description, serving to explain the principles of the disclosure.

[0038] [Figure 1] FIG. 1 is a schematic diagram of a bioabsorbable nanoparticle according to at least one embodiment.

[0039] [Diagram 2] FIG. 2 is a schematic diagram of a bioabsorbable nanoparticle including a surface polymer according to at least one embodiment.

[0040] [Diagram 3] FIG. 3 is a flow chart of a method for making the bioabsorbable nanoparticles of FIG. 1 according to at least one embodiment.

[0041] [Figure 4] FIG. 4 is a partial flow chart similar to FIG. 3 for making the bioabsorbable nanoparticles of FIG. 2 according to at least one embodiment.

[0042] [Diagram 5] FIG. 5 is a flow chart of a method of treating a patient with the bioabsorbable nanoparticles of FIGS. 1-2 according to at least one embodiment.

[0043] [Figure 6] FIG. 6 is a graphical representation showing the relationship between lipid loading level and nanoparticle diameter, according to at least one embodiment.

[0044] [Figure 7] FIG. 7 is a graphical representation showing the relationship between lipid levels and nucleotide loading, according to at least one embodiment.

[0045] [Figure 8] FIG. 8 is a graphical illustration of the relationship between lipid levels and zeta potential, according to at least one embodiment.

[0046] [Figure 9] FIG. 9 is a graphical diagram illustrating the relationship between incubation and nucleotide release for multiple trials, according to at least one embodiment. [Figure 10] FIG. 10 is a graphical diagram illustrating the relationship between incubation and nucleotide release for multiple trials, according to at least one embodiment.

[0047] [Figure 11] FIG. 11 shows particle distributions of TFF washed nanoparticles, deionized water (di-water) and reconstituted particles in phosphate buffered saline (PBS) according to at least one embodiment.

[0048] [Figure 12] FIG. 12 is a gel assay as described in the Examples according to at least one embodiment.

[0049] [Figure 13] FIG. 13 is a scanning electron micrograph (SEM) image of a bioabsorbable nanoparticle formed according to at least one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0050] Detailed Description Definitions and Terminology This disclosure is not to be construed in a limiting sense, for example, the terms used in this application should be interpreted broadly with respect to the meaning that those in the art would give such terms.

[0051] The term "about" or "approximately" means within an acceptable error range for a particular value as determined by one of ordinary skill in the art, which depends in part on the way in which the value is measured or determined, e.g., the limitations of the measurement system. For example, "about" can mean within one standard deviation or more than one standard deviation, as is customary in the art. Alternatively, "about" can mean within a range of up to 20%, up to 10%, up to 5%, or up to 1% of a given value. Alternatively, the term can mean within a certain number of times, such as within 5 times or within 2 times of a value. When a particular value is described in this application and claims, unless otherwise indicated, the term "about" should be assumed to mean within an acceptable error range for the particular value.

[0052] Description of Various Embodiments Those skilled in the art will readily appreciate that the various aspects of the present disclosure may be implemented by any number of methods and devices configured to perform the intended functions. It should also be noted that the accompanying drawings referenced herein are not necessarily drawn to scale and may be exaggerated to illustrate various aspects of the present disclosure, and in that regard, the drawings should not be construed as limiting.

[0053] Referring first to FIG. 1, a diagram of an exemplary bioabsorbable particle, nanoparticle 100, is shown. Nanoparticle 100 includes a surface 110, a polymer matrix 120, lipid 140, and nucleic acid 150. Although lipid 140 and nucleic acid 150 are shown separated from one another within nanoparticle 100, it is understood that lipid 140 is preferably complexed with nucleic acid 150 within nanoparticle 100. In an exemplary embodiment, nanoparticle 100 is about 300 nm or less in size. In another exemplary embodiment, nanoparticle 100 is about 100 nm to about 300 nm in size. In a most preferred embodiment, nanoparticle 100 is about 200 nm to about 300 nm in size. Although nanoparticle 100 is shown and described herein, the present disclosure also relates to microparticles having sizes greater than about 300 nm, such as about 500 nm, 750 nm, 1000 nm (1 μm) or greater. The nanoparticles 100 may also have a neutral or near-neutral charge, for example, a zeta potential of about -20mv to about +20mv. Alternatively, the nanoparticles 100 may have a zeta potential of about -10mv to about +10mv. Preferably, the neutral or near-neutral nanoparticles 100 may have a zeta potential of about 0mv.

[0054] It should be noted that FIG. 1 is only a representation of the nanoparticle 100, and the depiction of the lipids 140 and nucleic acid 150 as heterogeneous features within the polymer matrix 120 is for illustrative purposes only. The polymer matrix 120, lipids 140, and nucleic acid 150 can be fully or partially homogenous. Alternatively, the polymer matrix 120, lipids 140, and nucleic acid 150 can be fully or partially heterogeneous. The polymer matrix 120, lipids 140, and nucleic acid 150 can be fully or partially an emulsion. The polymer matrix 120, lipids 140, and nucleic acid 150 can be fully or partially in a suspension. The polymer matrix 120, lipids 140, and nucleic acid 150 can be fully or partially in any other mixture form as will be understood and appreciated by those skilled in the art. Furthermore, the polymer matrix 120, lipids 140, and nucleic acid 150 can be in any state of matter. For example, the nucleic acid 150 can be a solid or liquid encapsulated within the polymer matrix 120 (e.g., a solid polymer matrix). Each of the polymer matrix 120, lipids 140 and nucleic acids 150 is further described below.

[0055] In a non-limiting embodiment, the polymer matrix 120 of the nanoparticles 100 is a bioabsorbable or biodegradable polymer. The polymer matrix 120 can be hydrophobic in nature such that it degrades slower than hydrophilic matrices. The polymer matrix 120 can also exhibit low acid degradation to minimize inflammation. In one embodiment, the polymer matrix 120 can be a trimethylene carbonate (TMC) based polymer, such as a copolymer of TMC and polylactic acid (PLA) (hereinafter "PLA:TMC"). PLA:TMC copolymers can be synthesized using methods well known in the art, for example, by combining a TMC monomer with a suitable comonomer, such as lactic acid, e.g., L-lactic acid comonomer to form poly(L,lactic acid-TMC) (hereinafter "L-PLA:TMC"), by combining a D-lactic acid comonomer to form poly(D,lactic acid-TMC) (hereinafter "D-PLA:TMC"), or by combining L-lactic acid and D-lactic acid with TMC comonomer to form poly(DL,lactic acid-TMC) (hereinafter "D,L-PLA:TMC"). The PLA:TMC copolymer can have a weight ratio of D-PLA / TMC of 55% / 45% (55:45) or 75% / 25% (75:25), L-PLA / TMC of 55% / 45% (55:45) or 75% / 25% (75:25), and D,L-PLA / TMC of 50% / 50% (50:50) or 75% / 25% (75:25) (all by weight). In some embodiments, the PLA:TMC copolymer can include 45-60 wt% PLA and 40-55 wt% TMC. In another embodiment, the polymer matrix 120 can include a terpolymer of PLA, TMC, and another polymer, such as polyethylene glycol (PEG), hereinafter "PLA:TMC:PEG." In yet another embodiment, the polymer matrix 120 can include a poly(lactic-co-glycolic acid) (PLGA) copolymer that includes PLA and polyglycolic acid (PGA) comonomers.

[0056] The type of polymers used, the ratio of polymers used, and the method of manufacturing the polymer matrix 120 can all be altered to tailor the properties of the polymer matrix 120. Such properties can include the ability of the polymer matrix 120 to degrade or release the nucleic acid 150, the effect of pH on the polymer matrix 120, the size of the nanoparticles 100, the amount of lipid 140 and nucleic acid 150 loaded into the nanoparticles 100, the physical properties of the nanoparticles 100 (e.g., density, melting point, glass transition temperature, elastic modulus, etc.), and the chemical properties of the nanoparticles 100 (e.g., molecular weight, polarity, charge, etc.). In one embodiment, the polymer matrix 120 is formulated to degrade in the patient's digestive tract. In particular, the polymer matrix 120 can be formulated to degrade in the patient's colon.

[0057] In one embodiment, the lipid 140 of the nanoparticle 100 is a cationic lipid salt. In particular, the lipid 140 can be 1,2-dioleoyl-3-trimethylammonium-propane chloride salt (DOTAP) or 1,2-di-O-octadecenyl-3-trimethylammonium propane chloride salt (DOTMA). In other embodiments, any lipid 140 can be used. The nanoparticle 100 can be loaded with about 10 wt% to about 40 wt% lipid 140 or about 20 wt% to about 30 wt% lipid 140, although the amount of lipid 140 loaded into the nanoparticle 100 can be varied to adjust the properties of the nanoparticle 100, such as size, loading and / or release of nucleic acid 150, charge, zeta potential, etc. The loading of lipid 140 can be expressed as a ratio to the amount of polymer matrix 120. The nanoparticles 100 may be loaded with lipids 140 such that the lipid 140 / polymer matrix 120 mass ratio is about 1:4. The nanoparticles 100 may be loaded with lipids 140 such that the lipid 140 / polymer matrix 120 mass ratio is about 1:1. The nanoparticles 100 may be loaded with lipids 140 such that the lipid 140 / polymer matrix 120 mass ratio is about 1:2. The nanoparticles 100 may be loaded with lipids 140 such that the lipid 140 / polymer matrix 120 mass ratio is about 3:4. The loading amount of lipids 140 may also be expressed as a ratio to the amount of nucleic acid 150. The nanoparticles 100 may be loaded with lipids 140 such that the lipid 140 / nucleic acid 150 mass ratio is about 1:1. The nanoparticles 100 may be loaded with lipids 140 such that the lipid 140 / nucleic acid 150 mass ratio is about 2:1. The nanoparticles 100 may be loaded with lipids 140 such that the lipid 140 / nucleic acid 150 mass ratio is about 5:4. The nanoparticles 100 may be loaded with lipids 140 such that the lipid 140 / nucleic acid 150 mass ratio is about 7:4. The nanoparticles 100 may be loaded with lipids 140 such that the lipid 140 / nucleic acid 150 mass ratio is about 3:2. The loading of lipids 140 allows for more fine tuning of the properties of the nanoparticles 100. In general, an increase in the amount of lipids 140 loaded into the nanoparticles 100 corresponds to an increase in the loading amount of nucleic acid 150 and an increase in the zeta potential (FIGS. 7-8).It is typically desired that the nanoparticles 100 have a neutral or slight negative charge, although this can be altered depending on the loading and type of lipid 140 within the nanoparticles 100 .

[0058] The nucleic acid 150 of the nanoparticle 100 comprises a short chain of nucleotides. In some embodiments, the nucleic acid 150 is an oligonucleotide. Oligonucleotides are short DNA and / or RNA molecules and / or oligomers that have a wide range of applications in disease treatment, genetic testing and research. The use of oligonucleotides as therapeutic agents relies on their ability to interfere with the basic machinery of protein synthesis in a sequence-specific manner, either by binding to mRNA transcribed from a gene or by binding directly to a target gene. The oligonucleotide can be an antisense oligonucleotide (ASO). ASOs can be used to control gene expression and treat inflammatory and neoplastic diseases.

[0059] Oligonucleotides are characterized by the sequence and number of nucleotide residues that compose the entire molecule. The number of DNA and / or RNA nucleotide units that compose the molecule usually represents the length of the oligonucleotide. For example, an oligonucleotide of 10 nucleotides or bases is a "10-mer" oligonucleotide. Often, chemical modifications of the backbone or sugar ring are made, for example to enhance nuclease resistance or target specificity.

[0060] To avoid shearing the nucleic acid during the sonication process used to make the bioabsorbable particles, nucleic acids less than 75 nucleotides are preferred, and more preferably, the nucleic acid is less than 40 nucleotides.

[0061] The nanoparticles 100 can be loaded with at least 5 wt% nucleic acid 150, about 5 wt%, about 10 wt%, about 15 wt%, about 20 wt%, about 25 wt%, about 30 wt% or more nucleic acid 150, although this amount can be varied to tailor the properties of the nanoparticles 100.

[0062] The nanoparticles 100 are configured to degrade in the patient's digestive tract and release the nucleic acid 150 for medical treatment. In one example, the nanoparticles 100 are configured to be absorbed / degraded in the patient's colon, so that the nucleic acid 150 can be delivered directly into the colon to treat inflammatory bowel disease (Crohn's disease, ulcerative colitis, etc.). Additionally, the nanoparticles 100 may be configured to degrade, absorb, or release an active agent in any organ or at any point in the digestive tract (stomach, intestines, etc.) of the patient. In the illustrated embodiment, the nanoparticles 100 are loaded with nucleic acid 150 suitable for treating inflammatory bowel disease, but in other embodiments, the nanoparticles 100 may be loaded with nucleic acid 150 or any active ingredient or drug suitable for treating a wide variety of medical problems, including, but not limited to, cardiovascular disease, high blood pressure, chronic heart failure, diabetes, Parkinson's disease, prostate cancer, and chronic kidney disease.

[0063] Referring now to FIG. 2, another exemplary nanoparticle 100' is shown. The nanoparticle 100' of FIG. 2 is similar to the nanoparticle 100 of FIG. 1, with like reference numbers indicating like elements, except as described herein. As shown in FIG. 2, the nanoparticle 100' can also include a surface polymer 170'. In one embodiment, the surface polymer 170' is covalently attached to at least the surface 110' of the nanoparticle 100'. A non-limiting example of the surface polymer 170' is a copolymer of PLA and polyethylene glycol (PEG). When PEG is used as the surface polymer 170' (either alone or as a copolymer), the surface 110' can be described as being "PEGylated." The surface polymer 170' can be added to the surface 110' of the nanoparticle 100' by forming the nanoparticle 100' in the presence of a physical blend of the surface polymer 170' or by forming a terpolymer including the surface polymer 170' and the polymer matrix 120'. Additionally, the surface polymer 170' can be attached to the surface 110' via coupling groups located on the nanoparticles 100'. Non-limiting examples of such coupling groups include 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC), succinimidyl active ester, and NH2-PEG. In other embodiments, the surface polymer 170' can be attached to the surface 110' after the nanoparticles 100' are fabricated. The surface polymer 170' can aid in the movement of the nanoparticles 100', the bioabsorption of the nanoparticles 100', the degradation of the nanoparticles 100', or the alteration of the physical or chemical properties of the nanoparticles 100'. Each nanoparticle 100' can include at least about 1 wt%, at least about 5 wt%, at least about 10 wt%, at least about 15 wt%, or at least about 20 wt% of the surface polymer 170'. In some embodiments, each nanoparticle can comprise about 1 wt% to about 20 wt%, about 1 wt% to about 15 wt%, about 1 wt% to about 10 wt%, about 5 wt% to about 20 wt%, about 5 wt% to about 15 wt%, or about 5 wt% to about 10 wt%.

[0064] Referring now to Figure 3, a method 300 of making the nanoparticles 100 of Figure 1 is shown. The method 300 includes dissolving the structural polymer matrix 120 and lipid salts 140 in a suitable solvent 310, adding nucleic acid 150 and sonicating the mixture to form a water-in-oil emulsion 320, adding an aqueous solution such as polyvinyl alcohol 330, sonicating the resulting mixture to form a water-in-oil-in-water emulsion 340, adding water 350, collecting the nanoparticles 100 by drying, centrifugation or another suitable method 360, and washing the nanoparticles 100 370. While this method illustrates one way of making the nanoparticles 100, additional steps can be added to the method 300 including slowly shaking the water-in-oil emulsion for several hours, stirring the double emulsion overnight after adding water 350, dispersing the nanoparticles 100 in water after washing 370, and / or freeze-drying the nanoparticles 100 after washing 370, etc. The dissolving step 310 can be completed using any solvent that can effectively dissolve the polymer matrix 120 and lipids 140, such as, but not limited to, methylene chloride. The sonication steps 320, 340 can be performed on an ice bath. In other embodiments, sonication can be performed at different temperatures, for different times, and at different amplitudes. See Example 7 for an embodiment of the manufacturing method 300. Once the nanoparticles 100 are manufactured, they can be analyzed as known in the art and as described in the Examples below.

[0065] Referring now to Figure 4, a method 300' of manufacturing the nanoparticles 100' of Figure 2 is partially shown. The manufacturing method 300' shown in Figure 4 is similar to the manufacturing method 300 of Figure 3, and like reference numbers identify like elements, except as described herein. As shown in Figure 4, the surface polymer 170' is added to the polymer matrix 120' and lipid salt 140' during dissolution 310'.

[0066] Referring now to FIG. 5, a method of treatment 400 is shown. The method of treatment 400 is described with respect to the nanoparticles 100 of FIG. 1, however, the method of treatment 400 is equally applicable to the nanoparticles 100' of FIG. 2. The method of treatment 400 includes administering 410 the nanoparticles 100 to a patient, where the polymer matrix 120 degrades 420 within the patient, followed by releasing 430 the nucleic acid 430 from the nanoparticles 100 to the patient. The nanoparticles 100 can be administered orally 410 via a pill, tablet or solution, or by injection 410. When administered orally, the nanoparticles 100 can be initially placed in a capsule (not shown) that degrades at a point or specific area in the digestive tract. In one embodiment, the capsule has an enteric coating that allows the capsule to degrade in response to a change in pH.

[0067] The nanoparticles 100 are configured to be bioabsorbable so that the polymer matrix 120, lipids 140 and / or nucleic acids 150 are absorbed into the body. One possible method of absorption is by pinocytosis within the cell. In pinocytosis, the cell membrane stretches and folds around the extracellular material, forming a pouch forming an internalized vesicle. The vesicle eventually fuses with a lysosome, where the contents (in this case the nanoparticles 100) are digested. In this manner, the polymer matrix 120 can be degraded within the cells in the digestive tract through the cell's internal digestive process, after which the nucleic acid 150 is delivered to the cell. In this manner, the nucleic acid 150 can be delivered to a target area of ​​a patient to treat various diseases, such as irritable bowel syndrome, cardiovascular disease, high blood pressure, chronic heart failure, diabetes, Parkinson's disease, prostate cancer or chronic kidney disease.

[0068] Although the nanoparticles 100, 100' shown in Figures 1-2 and the method shown in Figures 3-5 are provided as examples of various features of the device / method, and combinations of these illustrated features are clearly within the scope of the present invention, the examples and their description are not intended to suggest that the inventive concepts provided herein are limited to one or more of the features shown in Figures 1-5, from fewer, additional, or alternative features. For example, in various embodiments, the method steps shown in Figure 5 can include steps described with reference to Figure 3. It is understood that the reverse is also true. Furthermore, one or more components shown in Figure 1 can be used in addition to or as a substitute for the components shown in Figure 2.

[0069] Test Method Although particular methods and apparatus are described below, it will be appreciated that other methods or apparatus may be substituted as deemed suitable by those skilled in the art.

[0070] intrinsic viscosity Intrinsic viscosity (IV) was measured using a Cannon MiniPV-HX automatic viscometer using hexafluoroisopropanol (HFIP) as the extraction solvent.

[0071] Nanoparticle Size Nanoparticle size was measured using an Ultrasizer (Marlven Panalytical) in multi-angle light scattering mode.

[0072] charge The zeta potential of the nanoparticle dispersions was measured using an Ultrasizer (Marlven Panalytical) in multi-angle light scattering mode.

[0073] Release of oligonucleotides The amount and rate of oligonucleotide release from the nanoparticles was determined by gel electrophoresis as detailed in Example 9.

[0074] PEG density characteristics The PEG content on the nanoparticle surface was measured by UV assay as detailed in Example 21. EXAMPLES

[0075] example Polymer synthesis The bioabsorbable polymers identified in Examples 1-5 were synthesized according to the methods described in "Analysis and Characterization of Absorbable DL-Lactide Trimethylene Carbonate Copolyesters," Journal of Material Science: Materials in Medicine 4 (1993) pp. 381-88.

[0076] Example 1: L-PLA:TMC copolymer properties This example describes a copolymer with a ratio of L-PLA:TMC of 75:25. Table 1 shows the characterization data of this example composition in the form of purified samples. To obtain the purified samples, L-PLA:TMC copolymers were dissolved in chloroform (CHCl3) at 2-5 wt%, precipitated with 10x isopropyl alcohol (IPA), and then vacuum dried. In this example, IV (HFIP) = 1.349 dL / g and the glass transition temperature of the polymer was determined to be 32.95°C.

[0077] Example 2: Characterization of D,L-PLA:TMC-PEG5K copolymer This example describes a copolymer D,L-PLA:TMC-PEG5K with a ratio of 86.4:8.7:4.9. Table 1 shows the characterization data for this composition. In this example, IV(HFIP)=1.3 dL / g and the glass transition temperature of the polymer was determined to be 31.7° C.

[0078] Example 3: Characterization of D,L-PLA:TMC-PEG5K copolymer This example describes the copolymer D,L-PLA:TMC-PEG5K in the ratio of 73.4:21.8:4.8. Table 1 shows the characterization data for this composition. In this example, IV(HFIP)=1.2 dL / g and the glass transition temperature of the polymer was determined to be 20.4° C.

[0079] Example 4: Characterization of D,L-PLA:TMC-PEG5K copolymer This example describes the copolymer D,L-PLA:TMC-PEG5K in a ratio of 82:8:10. Characterization data for this composition is shown in Table 1. In this example, IV(HFIP)=1.0 dL / g and the glass transition temperature of the polymer was determined to be 26.2° C.

[0080] Example 5: Characterization of D,L-PLA:TMC-PEG10K copolymer This example describes the copolymer D,L-PLA:TMC-PEG10K in a ratio of 86.5:8.5:5. Table 1 shows the characterization data for this composition. In this example, IV(HFIP)=1.4 dL / g and the glass transition temperature of the polymer was determined to be 34.5° C. [Table 1]

[0081] Example 6: Description of oligonucleotides This example describes the oligonucleotides utilized in the nanoparticle encapsulation example.

[0082] The oligonucleotide used for nanoparticle encapsulation, termed "Oligo-1," is a 20-mer oligonucleotide with 5 2'O-methylated nucleotides on both ends of the oligonucleotide.

[0083] The oligonucleotide used for nanoparticle encapsulation, designated "oligo-2," is unmethylated C*G*A*C*G*C*C*C*C*T*C*T*T*C*C*C*C*G*C*T*G, where asterisks indicate phosphorothioate linkages.

[0084] The oligonucleotide used for encapsulation of the nanoparticles, designated "Oligo-3," is mC*mG*mA*mC*mG*C*C*C*C*T*C*T*T*C*C*C*mC*mG*mC*T*mG, where methylation is indicated by "m" and the asterisk indicates a phosphorothioate linkage.

[0085] Example 7: Nanoparticles of Oligo-1 in L-PLA:TMC Copolymer with Low Levels of the Lipid Salt DOTAP This example demonstrates the encapsulation of Oligo-1 in L-PLA:TMC copolymer nanoparticles in the presence of low levels of the lipid salt DOTAP, specifically 19 wt% of the lipid salt DOTAP and a 1:1 ratio of the lipid salt DOTAP / Oligo-1, as described herein.

[0086] Nanoparticles were prepared by dissolving approximately 160 mg of L-PLA:TMC 75:25 ("LT-75") polymer (as described in Example 1) and 50 mg of lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride salt, Avanti Polar Lipids Inc) in 6 mL of methylene chloride at room temperature. 0.5 mL of 100 mg / mL Oligo-1 aqueous solution (DNase / RNase-free distilled water, Invitrogen) was pipetted into the polymer / DOTAP oil solution. The mixture was sonicated for 1 minute on an ice-water bath using a Branson SXF150 sonicator equipped with a ¼ inch tapered probe. Continuous mode with 45% amplitude was used for sonication. The water-in-oil (W / O) emulsion was placed on a shaker overnight at a speed of 100 rpm / min. The separated mixture was sonicated again for 1 minute on ice-water to produce a good dispersion. Next, about 15 mL of 5% polyvinyl alcohol (Aldrich, Mowiol 4-88) aqueous solution was added to the dispersion. The resulting mixture was sonicated for 2 minutes on an ice-water bath using the same sonicator and probe. Continuous mode was used for sonication at 45% amplitude to generate an oil-in-water emulsion. Next, 230 mL of deionized water was added to the emulsion with magnetic stirring at 500 rpm. The emulsion was stirred overnight at room temperature to remove the methylene chloride. This resulted in hardened nanoparticles, which were collected by centrifugation at 5000 rpm for 30 minutes at 4°C (Beckman-Coulter Avanti-J15R centrifuge). The nanoparticles were redispersed in 0.2 wt% polyvinyl alcohol solution and centrifuged again to remove residual chemicals. The supernatant was discarded. The washed nanoparticles were dispersed in 10 mL of deionized water. Approximately 1 mL of the dispersed nanoparticles was set aside for size and zeta potential characterization. The remaining dispersion was freeze-dried. A scanning electron microscope (SEM) image of the freeze-dried nanoparticles taken at 20,000x magnification is shown in Figure 13. The nanoparticles were determined to be spherical and single.

[0087] Example 8: Size and charge characterization of the nanoparticles of Example 7 This example shows the characterization of the size and zeta potential of nanoparticles formed according to Example 7.

[0088] The nanoparticle dispersions described in Example 7 were diluted 5-10 times with deionized water prior to testing. Characterization of the size and zeta potential of the nanoparticle dispersions was performed using dynamic light scattering using a Zetasizer Ultra (Malvern Panalytical, Malvern UK). The results are summarized in Table 2. The results are also shown in Figure 6, which shows the relationship between nanoparticle diameter (also called size) and the level of lipid loaded onto the nanoparticles. Figure 8 shows the relationship between zeta potential and the level of lipid loaded onto the nanoparticles.

[0089] Example 9: Oligonucleotide loading characterization of the nanoparticles of Example 7 This example describes a characterization assay for oligonucleotide loading of nanoparticles. The results are summarized in Table 2 and Figure 7.

[0090] The nanoparticles were weighed and dissolved in 1 mL of dimethyl sulfoxide (Sigma Aldrich). The nanoparticle / dimethyl sulfoxide (DMSO) solution was incubated in a 37°C water bath for 2 hours to allow complete dissolution of the nanoparticles. To decomplex the oligonucleotides from the lipid salts, 200 μL of the DMSO / nanoparticle solution was added to 500 μL of a solution of 100 mg / mL heparin (Sigma Aldrich) and 100 mM octyl BD-galactoside (Sigma Alrdich) in nuclease-free deionized water (Invitrogen). The solution was vortexed for 5 minutes at room temperature, placed on a shaker table for 30 minutes at room temperature, and vortexed for an additional 5 minutes before being run on an electrophoresis gel and quantified. For electrophoresis, two oligonucleotide standards were prepared at concentrations of 2 ng / μL and 1 ng / μL, respectively, in nuclease-free water (Invitrogen). The oligonucleotide standard solutions contained the same concentrations of heparin and octyl BD-galactoside as the nanoparticle samples to account for fluorescence due to the reagents. 10 μL of each sample or standard was placed in a microcentrifuge tube. 2 μL of 6X DNA Orange loading dye (Invitrogen) was added to each sample and mixed well. All 12 μL of each mixture was added to wells of a 10-well 4-20% TBE gel (Invitrogen) in 1X TBE buffer. The gels were run at 250V for 25 minutes. The gels were removed and stained with 1X Sybr Gold (50,000X stock diluted in 1X TBE buffer, Invitrogen) for 20 minutes with gentle rocking. The gels were imaged using Image Ready software (Biorad) on a BioRad Gel Doc system. A standard curve was generated using the standards in Image Ready software (Biorad) and the concentrations of the unknown samples were determined from the standard curve. The results are summarized in Table 2 and Figure 7 shows a representative study, illustrating the relationship between nucleic acid loading (wt%) and the level of lipid loaded into the nanoparticles.

[0091] Example 10: Nanoparticles of Oligo-1 in L-PLA:TMC Copolymer with Moderate Levels of the Lipid Salt DOTAP This example shows the encapsulation of Oligo-1 into L-PLA:TMC copolymer nanoparticles in the presence of moderate levels of the lipid salt DOTAP, specifically 26 wt% of the lipid salt DOTAP and a lipid salt DOTAP / Oligo-1 ratio of 3:2, as described herein.

[0092] Nanoparticles were prepared by dissolving approximately 220 mg of L-PLA:TMC75:25 polymer (as described in Example 1) and 100 mg of lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride salt, Avanti Polar Lipids Inc) in 8 mL of methylene chloride at room temperature. 0.5 mL of 130 mg / mL Oligo-1 aqueous solution (DNase / RNase free distilled water, Invitrogen) was pipetted into the polymer / DOTAP oil solution. Nanoparticles were made and washed following the same procedure as described in Example 7. The washed nanoparticles were dispersed in 10 mL of deionized water. Approximately 1 mL of dispersed nanoparticles was set aside for size and zeta potential characterization. The remaining dispersion was lyophilized.

[0093] Nanoparticle size and zeta potential were measured as described in Example 8, and oligonucleotide loading was measured as described in Example 9. The results are summarized in Table 2. Representative studies are shown in Figures 6-8.

[0094] Example 11: Nanoparticles of Oligo-1 in L-PLA:TMC Copolymer with High Levels of the Lipid Salt DOTAP This example demonstrates the encapsulation of Oligo-1 into L-PLA:TMC copolymer nanoparticles in the presence of high levels of the lipid salt DOTAP, specifically 32 wt% of the lipid salt DOTAP and a lipid salt DOTAP / Oligo-1 ratio of 2:1, as described herein.

[0095] Nanoparticles were prepared by dissolving approximately 160 mg of L-PLA:TMC75:25 polymer (as described in Example 1) and 100 mg of lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride salt, Avanti Polar Lipids Inc) in 6 mL of methylene chloride at room temperature. 0.5 mL of 100 mg / mL Oligo-1 aqueous solution (DNase / RNase free distilled water, Invitrogen) was pipetted into the polymer / DOTAP oil solution. Nanoparticles were prepared and washed following the same procedure as described in Example 7. The washed nanoparticles were dispersed in 10 mL of deionized water. Approximately 1 mL of dispersed nanoparticles was set aside for size and zeta potential characterization. The remaining dispersion was lyophilized.

[0096] Nanoparticle size and zeta potential were measured as described in Example 8, and oligonucleotide loading was measured as described in Example 9. The results are summarized in Table 2. Representative studies are shown in Figures 6-8.

[0097] Example 12: Nanoparticles of Oligo-1 in L-PLA:TMC Copolymer with Low Levels of the Lipid Salt DOTMA This example demonstrates the encapsulation of Oligo-1 into L-PLA:TMC copolymer nanoparticles in the presence of low levels of the lipid salt DOTMA as described herein.

[0098] Nanoparticles were prepared by dissolving approximately 160 mg of L-PLA:TMC75:25 polymer (as described in Example 1) and 50 mg of lipid salt DOTMA (1,2-di-O-octadecenyl-3-trimethylammonium propane chloride salt Avanti Polar Lipids Inc) in 6 mL of methylene chloride at room temperature. 0.5 mL of 100 mg / mL Oligo-1 aqueous solution (DNase / RNase free distilled water, Invitrogen) was pipetted into the polymer / DOTMA oil solution. Nanoparticles were prepared and washed following the same procedure as described in Example 7. The washed nanoparticles were dispersed in 10 mL of deionized water. Approximately 1 mL of dispersed nanoparticles was set aside for size and zeta potential characterization. The remaining dispersion was lyophilized.

[0099] Nanoparticle size and zeta potential were measured as described in Example 8, and oligonucleotide loading was measured as described in Example 9. The results are summarized in Table 2. Representative studies are shown in Figures 6-8.

[0100] Example 13: Nanoparticles of Oligo-1 in L-PLA:TMC Copolymer with High Levels of the Lipid Salt DOTMA This example demonstrates the encapsulation of Oligo-1 into L-PLA:TMC copolymer nanoparticles in the presence of high levels of the lipid salt DOTMA as described herein.

[0101] Nanoparticles were prepared by dissolving approximately 160 mg of L-PLA:TMC75:25 polymer (as described in Example 1) and 100 mg of lipid salt DOTMA (1,2-di-O-octadecenyl-3-trimethylammonium propane chloride salt Avanti Polar Lipids Inc) in 6 mL of methylene chloride at room temperature. 1 mL of 100 mg / mL Oligo-1 aqueous solution (DNase / RNase free distilled water, Invitrogen) was pipetted into the polymer / DOTAP oil solution. Nanoparticles were prepared and washed following the same procedure as described in Example 7. The washed nanoparticles were dispersed in 10 mL of deionized water. Approximately 1 mL of dispersed nanoparticles was set aside for size and zeta potential characterization. The remaining dispersion was lyophilized.

[0102] Nanoparticle size and zeta potential were measured as described in Example 8, and oligonucleotide loading was measured as described in Example 9. The results are summarized in Table 2. Representative studies are shown in Figures 6-8.

[0103] Example 14: Nanoparticles of Oligo-1 in PLGA Copolymers with Low Levels of the Lipid Salt DOTAP This example shows the encapsulation of Oligo-1 into PLGA copolymer nanoparticles in the presence of low levels of the lipid salt DOTAP as a comparison.

[0104] Nanoparticles were prepared by dissolving approximately 160 mg of PLGA polymer (Resomer® RG 756 S, poly(D,L-lactide-co-glycolide), purchased from Evonik Industries, Germany) and 50 mg of lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium propane chloride salt Avanti Polar Lipids Inc) in 6 mL of methylene chloride at room temperature. 0.5 mL of a 100 mg / mL aqueous solution of Oligo-1 (DNase / RNase free distilled water, Invitrogen) was pipetted into the polymer / DOTAP oil solution. Nanoparticles were produced and washed following the same procedure as described in Example 7. The washed nanoparticles were dispersed in 10 mL of deionized water. Approximately 1 mL of dispersed particles was set aside for size and zeta potential characterization. The remaining dispersion was freeze-dried.

[0105] The size and zeta potential of the nanoparticles were measured as described in Example 8, and the loading of oligonucleotides was measured as described in Example 9. The results are summarized in Table 2.

[0106] Example 15: Nanoparticles of Oligo-1 in PLGA Copolymers with High Levels of the Lipid Salt DOTAP This example shows the encapsulation of Oligo-1 into PLGA copolymer nanoparticles in the presence of high levels of the lipid salt DOTAP as a comparison.

[0107] Nanoparticles were prepared by dissolving approximately 160 mg of PLGA polymer (Resomer® RG 756 S, poly(D,L-lactide-co-glycolide), purchased from Evonik Industries, Germany) and 100 mg of lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride salt, Avanti Polar Lipids Inc) in 6 mL of methylene chloride at room temperature. 1 mL of 100 mg / mL Oligo-1 aqueous solution (DNase / RNase free distilled water, Invitrogen) was pipetted into the polymer / DOTAP oil solution. Nanoparticles were prepared and washed following the same procedure as described in Example 7. The washed nanoparticles were dispersed in 10 mL of deionized water. Approximately 1 mL of dispersed nanoparticles was set aside for size and zeta potential characterization. The remaining dispersion was freeze-dried.

[0108] Nanoparticle size and zeta potential were measured as described in Example 8, and oligonucleotide loading was measured as described in Example 9. The results are summarized in Table 2. Representative studies are shown in Figures 6-8. [Table 2]

[0109] Example 16: Release of oligonucleotides The release of encapsulated oligonucleotides at pH 7 and pH 4 and a summary of the results are shown in Figures 9-10, showing the amount of nucleic acid released as a percentage of theoretical loading and as a function of incubation time, as described herein.

[0110] To determine whether there is a burst release of encapsulated oligonucleotides at pH 7, 1 mL of 1 mg / mL oligonucleotide nanoparticle dispersion made according to Example 11 was incubated in phosphate buffered saline (PBS) solution supplemented with 10% fetal bovine serum at 37° C. for 30 minutes, 1 hour, 4 hours, or 24 hours. Samples for analysis were collected in two ways for comparison. In the first method, the incubated samples were taken directly from the test tube and run on an electrophoresis gel (solid line) as described in Example 9. This method takes into account that the nanoparticles are too large to enter the gel and that the amount detected in the gel is only the "free" oligonucleotide released in the assay. In the second method, the incubated samples were centrifuged at 10,000 rpm (Beckman Coulter) for 1 hour at 4° C. to separate the nanoparticles from the "free" oligonucleotides (dashed line). The supernatant of the centrifuged sample was then run on an electrophoresis gel. These two methods were used to determine whether either method artificially separates the oligonucleotides from the nanoparticles by force or current.

[0111] To confirm the release of encapsulated oligonucleotides at pH 4, 1 mL of a 1 mg / mL oligonucleotide nanoparticle dispersion made according to Example 11 was incubated in phosphate citrate buffer at pH 4. The remainder of the analysis, including incubation and gel electrophoresis, was the same as for the pH 7 sample.

[0112] Example 17: Nanoparticles of Oligo-1 in L-PLA:TMC and PLA-PEG copolymers containing the lipid salt DOTAP This example demonstrates the encapsulation of Oligo-1 oligonucleotides into PLA-TMC and PLA-PEG, 2K-5K copolymer nanoparticles in the presence of the lipid salt DOTAP.

[0113] Nanoparticles were prepared by dissolving approximately 120 mg of L-PLA:TMC75:25 polymer (as described in Example 1), 40 mg of PLA-PEG copolymer (Sigma, methoxypoly(ethylene glycol)-b-poly(D,L-lactide), Mw=2K-5K) and 100 mg of lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride salt, Avanti Polar Lipids Inc) in 6 mL of methylene chloride at room temperature. One mL of 100 mg / mL Oligo-1 oligonucleotide aqueous solution (DNase / RNase free distilled water, Invitrogen) was pipetted into the polymer / DOTAP oil solution. The mixture was sonicated for 1 min in an ice-water bath using a Branson SXF150 sonicator equipped with a ¼ inch tapered probe. Continuous mode at 45% amplitude was used for sonication. The water-in-oil (W / O) emulsion was placed on a shaker at 100 rpm / min overnight. The separated mixture was sonicated again in ice water for 1 min to produce a good dispersion.

[0114] Next, about 15 mL of 0.5 wt / v% cholic acid (Sigma) in water was added to the dispersion. The resulting mixture was sonicated in an ice-water bath for 1 min using the same sonicator and probe. Continuous mode at 45% amplitude was used for sonication to generate an oil-in-water emulsion. Further, 230 mL of deionized water was added to the emulsion with magnetic stirring at 500 rpm. The emulsion was stirred overnight at room temperature to remove the methylene chloride. This resulted in hardened nanoparticles, which were collected by centrifugation (Beckman Coulter centrifuge) at 5000 rpm for 30 min at 4 °C. The nanoparticles were redispersed in deionized water and centrifuged again to remove residual chemicals. The supernatant was discarded. The washed nanoparticles were dispersed in 10 mL of deionized water. About 1 mL of the dispersed nanoparticles was set aside for size and zeta potential characterization. The remaining dispersion was freeze-dried.

[0115] The size and zeta potential of the nanoparticles were measured as described in Example 8, and the loading of oligonucleotides was measured as described in Example 9. The results are summarized in Table 4.

[0116] Example 18: Cleaning of particles using a tangential flow filtration system This example illustrates the cleaning process used to clean nanoparticles without causing particle coagulation.

[0117] Here, tangential flow filtration technology is used to wash and concentrate the nanoparticle emulsion. The system uses a Minimate EVO system, product ID: OAPMPUNV, from Pall Corporation (Port Washington, NY), equipped with a membrane module MIDIKROS 20CM 500K MPES 0.5MM FLL x FLL, Repligen Corporation (Waltham, MA), product ID: D02-E500-05-N, mPES membrane, 500 kD, 20 cm. The particle emulsion is first concentrated from 400 mL to 30 mL. Then, 70 mL of deionized water is added to the concentrated emulsion under stirring. The emulsion is concentrated again to 30 mL. This process is repeated twice. The third time, the emulsion is concentrated from 100 mL to approximately 15 mL. The washed particle emulsion is then pumped into a clean centrifuge tube.

[0118] Example 19: Oligo-2 nanoparticles in L-PLA:TMC with lipid salt DOTAP This example demonstrates the encapsulation of Oligo-2 oligonucleotides into PLA-TMC copolymer nanoparticles in the presence of the lipid salt DOTAP.

[0119] Nanoparticles were prepared by dissolving approximately 160 mg of L-PLA:TMC75:25 polymer (as described in Example 1) and 100 mg of lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride salt, Avanti Polar Lipids Inc) in 6 mL of methylene chloride at room temperature. 1 mL of 100 mg / mL Oligo-2 oligonucleotide aqueous solution (DNase / RNase free distilled water, Invitrogen) was pipetted into the polymer / DOTAP oil solution. The mixture was sonicated for 1 min on an ice-water bath using a Branson SXF150 sonicator equipped with a 1 / 4 inch tapered probe. Continuous mode was used for sonication with an amplitude of C45%. The water-in-oil (W / O) emulsion was placed on a shaker overnight at a speed of 100 rpm / min. The separated mixture was sonicated again for 1 min on ice-water to produce a good dispersion. Approximately 15 mL of 0.5 wt / v% cholic acid (Sigma) in water was then added to the dispersion. The resulting mixture was sonicated for 1 min on an ice-water bath using the same sonicator and probe. Continuous mode was used for sonication at 45% amplitude to create an oil-in-water emulsion. Further, 230 mL of deionized water was added to the emulsion with magnetic stirring at 500 rpm. The emulsion was stirred overnight at room temperature to remove the methylene chloride. This resulted in hardened nanoparticles, which were washed using the method described in Example 18. Approximately 1 mL of the dispersed nanoparticles was set aside for size and zeta potential characterization. The remaining dispersion was lyophilized in the presence of trehalose (Sigma) at a particle to trehalose mass ratio of 1:10 and 5 mM histidine buffer at pH 4.0 in the particle dispersion.

[0120] The lyophilized particles were reconstituted in both deionized water and PBS. No aggregation was observed in the reconstituted dispersion in either deionized water or PBS. The particle distribution is shown in Figure 11.

[0121] The size and zeta potential of the nanoparticles after washing and reconstitution were measured as described in Example 8, and the loading of oligonucleotides was measured as described in Example 9. The results are summarized in Table 4.

[0122] Example 20: Nanoparticles of Oligo-3 in L-PLA:TMC with lipid salt DOTAP This example demonstrates the encapsulation of Oligo-3 oligonucleotides into PLA-TMC copolymer nanoparticles in the presence of the lipid salt DOTAP.

[0123] Nanoparticles were prepared by dissolving approximately 160 mg of L-PLA:TMC75:25 polymer (as described in Example 1), 100 mg of lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride salt, Avanti Polar Lipids Inc) in 6 mL of methylene chloride at room temperature. 1 mL of 100 mg / mL Oligo-3 oligonucleotide aqueous solution (DNase / RNase free distilled water, Invitrogen) was pipetted into the polymer / DOTAP oil solution. The mixture was sonicated for 1 min on an ice-water bath using a Branson SXF150 sonicator with a 1 / 4 inch tapered probe. Continuous mode with an amplitude C45% was used for sonication. The water-in-oil (W / O) emulsion was placed on a shaker and agitated overnight at a speed of 100 rpm / min. The separated mixture was sonicated again for 1 min on ice-water to produce a good dispersion. Next, about 15 mL of 0.5 wt / v% aqueous cholic acid (Sigma) was added to the dispersion. The resulting mixture was sonicated in an ice-water bath for 1 min using the same sonicator and probe. Continuous mode was used for sonication at 45% amplitude to generate an oil-in-water emulsion. Further, 230 mL of deionized water was added to the emulsion with magnetic stirring at 500 rpm. The emulsion was stirred overnight at room temperature to remove the methylene chloride. This resulted in hardened nanoparticles, which were washed using a tangential flow filtration system as described in Example 18. About 1 mL of dispersed nanoparticles was set aside for size and zeta potential characterization. The remaining dispersion was freeze-dried as described in Example 19.

[0124] The size and zeta potential of the nanoparticles were measured as described in Example 8, and the loading of oligonucleotides was measured as described in Example 9. The results are summarized in Table 4.

[0125] Example 21: Characterization of PEG surface density and coverage on PLA-TMC-PEG particles This example describes the characterization of the PEG content on the surface of nanoparticles made from the polymers of Examples 2, 3 and 5.

[0126] PEGylated nanoparticles were prepared by dissolving approximately 160 mg of L-PLA:TMC-PEG5K 86.4:8.7:4.9 polymer (as described in Example 2) in 6 ml of methylene chloride at room temperature. Approximately 15 mL of 0.5 wt / v% cholic acid (Sigma) in water was then added to the polymer methylene chloride solution. The resulting mixture was sonicated for 1 min on an ice-water bath using the same sonicator and probe. Continuous mode was used for sonication at 45% amplitude to generate an oil-in-water emulsion. Additionally, 230 mL of deionized water was added to the emulsion while magnetically stirring at 500 rpm. The emulsion was stirred overnight at room temperature to remove the methylene chloride. This resulted in hardened nanoparticles that were washed using a tangential flow filtration system as described in Example 18.

[0127] PEGylated nanoparticles were also prepared from L-PLA:TMC-PEG5K polymer 73.4:21.8:4.8 (as described in Example 3) and L-PLA:TMC-PEG10K polymer 86.5:8.5:5 (as described in Example 5) in the same manner as described above. The PEG content on the nanoparticles was detected using a UV assay based on the complexation reaction of PEO with molybdophosphate. The PEG concentration was determined from the difference in absorbance of the blank and test solutions using a calibration curve. According to Koopal et al. ("Effect of Polyethylene Oxide Molecular Weight on the Measurement of Concentration in Aqueous Solutions", Talanta, 1982, Vol. 29, p. 495-501), this method is independent of the PEO molecular weight. Therefore, a calibration curve was established using different concentrations (10-500 μg / mL) of PEG with molecular weight 5K. Blanks were obtained from deionized water.

[0128] The tested PEG content of each batch of nanoparticles is shown in Table 3. The PEG content on the particles is close to the content in the polymer, which means that most of the PEG is on the surface of the particles. [Table 3]

[0129] Example 22: Nanoparticles of Oligo-2 in L-PLA:TMC-PEG Copolymer with the Lipid Salt DOTAP This example demonstrates the encapsulation of a model Oligo-2 oligonucleotide into PLA-TMC-PEG terpolymer nanoparticles in the presence of the lipid salt DOTAP.

[0130] Nanoparticles were prepared by dissolving approximately 100 mg of L-PLA:TMC:PEG73.4:21.8:4.8 terpolymer (as described in Example 3) and 100 mg of lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride salt, Avanti Polar Lipids Inc) in 6 mL of methylene chloride at room temperature. 1 mL of 100 mg / mL Oligo-2 aqueous solution (DNase / RNase free distilled water, Invitrogen) was pipetted into the polymer / DOTAP oil solution. Nanoparticles were prepared and washed following the same procedure as described in Example 18. Approximately 1 mL of dispersed nanoparticles was set aside for size and zeta potential characterization. The remaining dispersion was lyophilized in the presence of trehalose (Sigma) to a particle / trehalose mass ratio of 1:5. The lyophilized particles were also reconstituted in deionized water and PBS. No particle aggregation was observed in either deionized water or PBS.

[0131] The size and zeta potential of the nanoparticles were measured as described in Example 8, and the loading of oligonucleotides was measured as described in Example 9 with minor modifications. The particles were first dispersed in acetone and left at room temperature for at least 30 minutes. Then, DMSO was added to dissolve the particles. The ratio of DMSO to acetone is 4:1 by volume. A transparent particle DMSO / acetone solution was obtained for gel electrophoresis. The PEG density on the nanoparticle surface was measured as described in Example 21. It can be corrected according to the predictions in Example 28. The results are summarized in Table 4.

[0132] Example 23: Nanoparticles of Oligo-3 in L-PLA:TMC-PEG Copolymer with Lipid Salt DOTAP This example demonstrates the encapsulation of a model oligonucleotide, Oligo-3, into PLA-TMC-PEG terpolymer nanoparticles in the presence of the lipid salt DOTAP.

[0133] Nanoparticles were prepared by dissolving approximately 100 mg of L-PLA:TMC:PEG73.4:21.8:4.8 terpolymer (as described in Example 3) and 100 mg of lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride salt, Avanti Polar Lipids Inc) in 6 mL of methylene chloride at room temperature. 1 mL of 100 mg / mL Oligo2 aqueous solution (DNase / RNase free distilled water, Invitrogen) was pipetted into the polymer / DOTAP oil solution. Nanoparticles were made and washed following the same procedure as described in Example 18. Approximately 1 mL of dispersed nanoparticles was set aside for size and zeta potential characterization. The remaining dispersion was lyophilized as described in Example 22.

[0134] The size and zeta potential of the nanoparticles were measured as described in Example 8, and the loading of oligonucleotides was measured as described in Example 9 with minor modifications. The particles were first dispersed in acetone and left at room temperature for at least 30 minutes. Then, DMSO was added to dissolve the particles. The ratio of DMSO / acetone is 4:1. A transparent particle DMSO / acetone solution was obtained for gel electrophoresis. The PEG density on the nanoparticle surface was measured as described in Example 21. It can be corrected according to the predictions in Example 28. The results are summarized in Table 4.

[0135] Example 24: Nanoparticles of Oligo-3 in PEG:L-PLA:TMC Copolymer with Lipid Salt DOTMA This example demonstrates the encapsulation of a model oligonucleotide, Oligo-3, into PLA-TMC-PEG terpolymer nanoparticles in the presence of the lipid salt DOTAP.

[0136] Nanoparticles were prepared by dissolving approximately 100 mg of L-PLA:TMC:PEG73.4:21.8:4.8 terpolymer (as described in Example 3) and 100 mg of lipid salt DOTMA (1,2-di-O-octadecenyl-3-trimethylammonium propane chloride salt Avanti Polar Lipids Inc) in 6 mL of methylene chloride at room temperature. 1 mL of a 100 mg / mL aqueous solution of Oligo-2 (DNase / RNase free distilled water, Invitrogen) was pipetted into the polymer / DOTAP oil solution. Nanoparticles were prepared and washed following the same procedure as described in Example 18. Approximately 1 mL of dispersed nanoparticles was set aside for size and zeta potential characterization. The remaining dispersion was lyophilized as described in Example 22.

[0137] The size and zeta potential of the nanoparticles were measured as described in Example 8, and the loading of oligonucleotides was measured as described in Example 9 with minor modifications. The particles were first dispersed in acetone and left at room temperature for at least 30 minutes. DMSO was then added to dissolve the particles. The ratio of DMSO / acetone was 4:1 by volume. A transparent DMSO / acetone solution of particles was obtained for gel electrophoresis. The PEG density on the nanoparticle surface was measured as described in Example 21, and can be corrected according to the predictions in Example 28. The results are summarized in Table 4.

[0138] Example 25: Nanoparticles of Oligo-2 in PEG:L-PLA:TMC Copolymer with the Lipid Salt DOTAP This example demonstrates the encapsulation of Oligo-2 into PEG-PLA-TMC terpolymer nanoparticles in the presence of the lipid salt DOTAP.

[0139] This example demonstrates the encapsulation of a model Oligo-2 oligonucleotide into PLA-TMC-PEG terpolymer nanoparticles in the presence of the lipid salt DOTAP.

[0140] Nanoparticles were prepared by dissolving approximately 100 mg of L-PLA:TMC:PEG86.5:8.5:5 terpolymer (as described in Example 5) and 100 mg of lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride salt, Avanti Polar Lipids Inc) in 6 mL of methylene chloride at room temperature. 1 mL of 100 mg / mL Oligo-2 aqueous solution (DNase / RNase free distilled water, Invitrogen) was pipetted into the polymer / DOTAP oil solution. Nanoparticles were made and washed following the same procedure as described in Example 18. Approximately 1 mL of dispersed nanoparticles was set aside for size and zeta potential characterization. The remaining dispersion was freeze-dried as described in Example 22.

[0141] The size and zeta potential of the nanoparticles were measured as described in Example 8, and the loading of oligonucleotides was measured as described in Example 9 with some modifications. The particles were first dispersed in acetone and left at room temperature for at least 30 minutes. Then, DMSO was added to dissolve the particles. The ratio of DMSO / acetone is 4:1 by volume. A transparent particle DMSO / acetone solution for gel electrophoresis was obtained. The PEG density on the nanoparticle surface was measured as described in Example 21. It can be corrected according to the prediction Example 28. The results are summarized in Table 4.

[0142] Example 26: Nanoparticles of Oligo-2 in PEG:L-PLA:TMC and LT75 Copolymers with Lipid Salt DOTAP This example shows the encapsulation of Oligo-2 into PEG-PLA-TMC and LT75 copolymer nanoparticles in the presence of the lipid salt DOTAP.

[0143] Nanoparticles were prepared by dissolving approximately 80 mg of L-PLA:TMC:PEG(5K) 82:8:10 polymer (as described in Example 4) and 100 mg of lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride salt, Avanti Polar Lipids Inc) in 6 mL of methylene chloride at room temperature. 1 mL of a 100 mg / mL model oligo-2 oligonucleotide aqueous solution (DNase / RNase free distilled water, Invitrogen) was pipetted into the polymer / DOTAP oil solution. Nanoparticles were made and washed following the same procedure as described in Example 16. The washed nanoparticles were dispersed in 10 mL of deionized water. Approximately 1 mL of the dispersed nanoparticles was set aside for size and zeta potential characterization. The remaining dispersion was lyophilized as described in Example 22.

[0144] The size and zeta potential of the nanoparticles were measured as described in Example 7, and the loading of oligonucleotides was measured as described in Example 9 with minor modifications. The particles were first dispersed in acetone and left at room temperature for at least 30 minutes. DMSO was then added to dissolve the particles. The ratio of DMSO / acetone is 4:1. A transparent particle DMSO / acetone solution for gel electrophoresis was obtained. The PEG content on the nanoparticle surface was measured as described in Example 21. The high PEG content tested indicates that the reagent is complexed with oligo and / or lipid salts and can be corrected according to the predictions Example 28. The results are summarized in Table 4. [Table 4] *Low content due to variability in assay development as discussed in Example 17 These measured PEG wt% values ​​obtained in Examples 22, 23, 24, 25 and 26 can be corrected according to Predictive Example 28.

[0145] Example 27: Gel Extraction Assay FIG. 12 shows the nanoparticle standards, extraction and gel assay of a particular example as described in the examples above.

[0146] Prophetic Example 28: Determination of Background Readings for PEG Surface Density and Coverage Assays This example shows how to determine background readings for PEG surface density and coverage assays so that the initial PEG readings can be adjusted with the background readings. Background readings can arise from non-specific binding in the assay and therefore will be positive for PEG when not present. This correction provides a more accurate correction of PEG surface density and coverage for particles produced with PLA-PEG or PLA-TMC-PEG. Background readings are based on particles without LT-75, ASO, lipid salts and PEG.

[0147] In the case of nanoparticles containing Oligo-2 and DOTAP, nanoparticles of LT-75, Oligo-2 and DOTAP are prepared (as described in Example 19) and analyzed for PEG surface density and coverage by assay (as described in Example 21) to determine the background reading of PEG.

[0148] To estimate the correction for PEG surface density and coverage, the values ​​obtained for background readings are subtracted from the nanoparticles containing PEG.

[0149] The invention of this application has been described above generally and with reference to specific embodiments. It is apparent to those skilled in the art that various modifications and variations can be made to the embodiments without departing from the scope of the disclosure. Therefore, the embodiments are intended to cover the modifications and variations of the present invention within the scope of the appended claims and their equivalents.

Claims

1. A plurality of bioabsorbable particles, each of which comprises: Polymer matrix, an antisense oligonucleotide (ASO) encapsulated within the polymer matrix; and a cationic lipid encapsulated within said polymer matrix; wherein the plurality of bioabsorbable particles comprises at least about 1 weight percent of an antisense oligonucleotide (ASO).

2. 2. The formulation of claim 1, wherein the plurality of bioabsorbable particles has an average particle size of less than 300 nm.

3. The formulation of any one of claims 1-2, wherein the plurality of bioabsorbable particles comprises at least about 5 weight percent ASO.

4. The formulation of any one of claims 1 to 3, wherein the plurality of bioabsorbable particles comprises at least about 10 weight percent ASO.

5. The formulation of any one of claims 1 to 4, wherein the plurality of bioabsorbable particles comprises at least about 15 weight percent ASO.

6. The formulation of any one of claims 1 to 5, wherein the polymer matrix comprises trimethylene carbonate (TMC).

7. The formulation of any one of claims 1 to 6, wherein the polymer matrix comprises a copolymer of TMC and polylactic acid (PLA).

8. 8. The formulation of claim 7, wherein the ratio of TMC / PLA is about 25 / 75.

9. The formulation of any one of claims 1 to 8, wherein the polymer matrix comprises poly(lactic-co-glycolic acid) (PLGA) copolymer.

10. The formulation of any one of claims 1 to 9, further comprising a surface polymer attached to a surface of each of the bioabsorbable particles.

11. The formulation of claim 10 , wherein the surface polymer comprises polyethylene glycol (PEG).

12. The formulation of claim 11 , wherein the bioabsorbable particles comprise at least 5 weight percent PEG.

13. The formulation of any one of claims 1 to 12, wherein the plurality of bioabsorbable particles comprises from about 10 weight percent to about 40 weight percent cationic lipid.

14. The formulation of any one of claims 1 to 13, wherein the plurality of bioabsorbable particles comprises about 20 weight percent to about 30 weight percent cationic lipid.

15. The formulation of any one of claims 1 to 14, wherein the plurality of bioabsorbable particles comprises nanoparticles.

16. The formulation of any one of claims 1 to 14, wherein the plurality of bioabsorbable particles comprises microparticles.

17. Delivering to a patient a formulation according to any one of claims 1 to 16; and allowing sufficient time for the polymer matrix to degrade within the patient and release the nucleic acid within the patient; A method of treating a patient in need of treatment, comprising the steps of:

18. (a) dissolving a structural polymer and a cationic lipid in a solvent; (b) adding a nucleic acid of 2 to 75 nucleotides in length to the dissolved structural polymer and cationic lipid; (c) sonicating the mixture of the structural polymer, the cationic lipid and the nucleic acid in a first sonication to create a water-in-oil emulsion; (d) adding an aqueous solution to the water-in-oil emulsion; (e) sonicating the water-in-oil emulsion with a second sonication to produce a water-in-oil-in-water emulsion; (f) adding water to the water-in-oil-in-water emulsion; (g) collecting a plurality of particles from the water-in-oil-in-water emulsion; and (h) washing the plurality of particles; 23. A method for producing a bioabsorbable particle formulation comprising:

19. 20. The method of claim 18, wherein said cationic lipid and said structural polymer are dissolved in a mass ratio of about 1:4 to about 1:

1.

20. 20. The method of claim 18 or 19, wherein the nucleic acid is an antisense oligonucleotide (ASO) and is supported on the plurality of particles at about 5 percent to about 20 percent by weight.

21. The method of any one of claims 18 to 20, wherein the first sonication and the second sonication are completed in an ice bath.

22. The method according to any one of claims 18 to 21, wherein the aqueous solution is a polyvinyl alcohol solution.

23. The method of any one of claims 18 to 22, wherein the step of collecting the plurality of particles from the emulsion is completed by centrifugation.

24. 24. The method of any one of claims 18 to 23, further comprising lyophilizing the oil solution in the presence of a sugar and a buffer.

25. 25. The method of claim 24, wherein the sugar is trehalose.

26. The method according to any one of claims 24 to 25, wherein the buffer is histidine.

27. (a) delivering to a patient a plurality of particles, each particle comprising: (i) a polymer matrix; (ii) a nucleic acid encapsulated within the polymer matrix, the nucleic acid being 2-75 nucleotides in length; and (iii) a cationic lipid encapsulated within the polymer matrix; wherein the ratio of the cationic lipid to the polymer matrix in each particle is from about 1:4 to about 1:1 by weight; and (b) allowing sufficient time for the polymer matrix to biodegrade within the patient and release the nucleic acid; A method of treating a patient in need of treatment, comprising:

28. 28. The method of claim 27, wherein the nucleic acid is an antisense oligonucleotide (ASO) loaded onto the plurality of particles at about 5 weight percent to about 20 weight percent, and the cationic lipid is either 1,2-di-O-octadecenyl-3-trimethylammonium propane chloride salt (DOTMA) or 1,2-dioleoyl-3-trimethylammonium propane chloride salt (DOTAP).

29. 29. The method of claim 27 or 28, wherein the polymer matrix biodegrades in the patient's colon.

30. 30. The method of any one of claims 27 to 29, wherein each particle further comprises a surface polymer on a surface of each particle, said surface polymer comprising polyethylene glycol (PEG).

31. 31. The method of claim 30, wherein each particle comprises at least 5 wt% PEG.

32. The method of any one of claims 27 to 31, wherein the plurality of particles comprises nanoparticles.

33. The method of any one of claims 27 to 32, wherein the patient has inflammatory bowel disease, cardiovascular disease, hypertension, chronic heart failure, diabetes, Parkinson's disease, prostate cancer, or chronic kidney disease.

34. A plurality of bioabsorbable particles, each of which comprises: (a) a polymer matrix; (b) a nucleic acid encapsulated within the polymer matrix; (c) a cationic lipid encapsulated within the polymer matrix; and (d) a surface polymer attached to the surface of each of the bioabsorbable particles; wherein the surface polymer comprises polyethylene glycol (PEG), and each of the bioabsorbable particles comprises at least 5 weight percent PEG.

Citation Information

Patent Citations

  • Injectable and biodegradable polymeric formulations for the controlled release of bioactive agents

    JP2020512339A

  • Encapsulated nanoparticles for drug delivery

    US20090312402A1